Traffic calming policy can reduce inequalities in child pedestrian injuries: database study - Sarah Jones; Ronan A Lyons; Ann John; Stephen Palmer (2005)
Objectives: To determine whether area wide traffic calming distribution reflects known inequalities in child pedestrian injury rates. To determine whether traffic calming is associated with changes in childhood pedestrian injury rates. Design: Small area ecological study, longitudinal analysis of injury rates with cross sectional analysis of traffic calming and method of travel to school. Settings: Two cities in the United Kingdom. Participants: 4–16 year old children between 1992 and 2000. Main outcome measures: Area wide traffic calming distribution by area deprivation status and changes in injury rate/1000. Results: The most deprived fourth of city A had 4.8 times (95% CI 3.71 to 6.22) the number of traffic calming features per 1000 population compared with the most affluent fourth. Injury rates among the most deprived dropped from 9.42 to 5.07 from 1992–94 to 1998–2000 (95% CI for change 2.82 to 5.91). In city B, the traffic calming ratio of the most to least deprived fourth was 1.88 (95% CI 1.46 to 2.42); injury rates in the deprived areas dropped from 8.92 to 7.46 (95% CI for change −0.84 to 3.77). Similar proportions of 9–12 year olds walked to school in both cities. Conclusions: Area wide traffic calming is associated with absolute reductions in child pedestrian injury rates and reductions in relative inequalities in child pedestrian injury rates.